Killing the Indian maiden : images of Native American women in film - Marubbio, M. Elise, 1963- (Lexington, Ky. : University Press of Kentucky, 2006)
Killing the Indian Maiden examines the fascinating and often disturbing portrayal of Native American women in film. M. Elise Marubbio examines the sacrificial role in which a young Native woman allies herself with a white male hero and dies as a result of that choice. In studying thirty-four Hollywood films from the silent period to the present, she draws upon theories of colonization, gender, race, and film studies to ground her analysis in broader historical and sociopolitical context and to help answer the question, "What does it mean to be an American?" The book reveals a cultural iconogra.
Emergence of the celluloid maiden -- The celluloid princess. Death, gratitude, and the squaw man's wife : the celluloid princess from 1908 to 1931 -- White-painted lady : the 1950s celluloid princess -- The sexualized maiden. What lies beneath the surface : the sexualized maiden of the 1940s -- The only good Indian is a dead Indian : the sexualized maiden of the 1950s and 1960s -- The hybrid celluloid maiden. Free love and violence : "going Native ' with the celluloid maiden in the 1970s -- Ghosts and vanishing Indian women : death of the celluloid maiden in the 1990s -- Into the twenty-first century.
Filmography: pages 233-239.
Includes bibliographical references (pages 271-283) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Indian women in motion pictures; Femmes des Peuples autochtones au cinéma.; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Indian women in motion pictures; Indianerin; Film; USA; Amerika; Frau -- Motiv -- Film -- USA; Film -- Motiv -- Frau -- USA; Film -- Motiv -- Indianerin -- USA; Indianerin -- Motiv -- Film -- USA; Film -- Motiv (Kunst) -- Indianerin -- Geschichte; Indianerin -- Motiv (Kunst) -- Film -- Geschichte